International integration and corporate governance practices in Russia - Yukhanaev, A.; Nguyen, T.; Demirbas, D.; Galvin, Peter (IGI Global, 2014)
This chapter considers the institutional environment in Russia, its potential impact upon governance practices, and the attitudes of Russian executives towards the alignment of governance processes relative to international standards. Focusing on corporate board directorship, the research addresses the extent that the harmonization of governance to international standards may assist boards of directors to improve their corporate development. Using a survey questionnaire, the authors explore perceptions of directors of public companies concerning the challenges of corporate governance development in the country. The study illustrates unanimity among the respondents about the reforms needed for international convergence of corporate governance standards. The results reveal that institutional alignment with good governance principles will foster strategic corporate development in the Russian economy. The study offers insights to policymakers in terms of enhancing legitimacy of corporate governance in the Russian context and provides a perspective for executives of foreign companies considering investment in the country.